Theoretical study on hole evolution of inclination finite thickness metal plate impacted by shaped charge jet. (May 2022) - Tan, Yaping; Huang, Zhengxiang; Xiao, Qiangqiang; Zu, Xudong; Xu, Mengwen
Highlights: A theoretical model of the hole evolution on the inclined thin target impacted by a shaped charge jet is derived, and the influence of the inclined angle on the initial pressure distribution and the final radii of the crater is discussed. The modified equation of target resistance strength as a function of the inclined angle is proposed. It is theoretically verified that the major axis and minor axis increase with the increase of the oblique angle. Interestingly, the offset between the minor axis and the geometric center of G is gradually significant with the increase of the oblique angle. The most important thing is that the radius in the downstream direction is greater than that in the upstream direction for oblique penetration, and the difference between them is more and more obvious with the increases of the oblique angle. Abstract: In the armor design field, the asymmetric interaction between various hypervelocity penetrators and the inclined targets is an important topic. However, most existing studies overlook the influence of asymmetry on the expansion of the initial penetration hole. A modified theoretical model for predicting the hole radii of hypervelocity penetrator impacting an inclined thin plate was derived in this research. According to a set of experimental results, the empirical parameters of the resistance strength term as a function of the oblique angle in this model were obtained. The theoretical predictions have excellent agreement with a series of simulation results as performed with an ANSYS/AUTODYN solver.